The Low-Frequency Fluctuation of Trial-by-Trial Frontal Theta Activity and Its Correlation With Reaction-Time Variability in Sustained Attention - Wang, Yao-Yao; Sun, Li; Liu, Yi-Wei; Pan, Jia-Hui; Zheng, Yu-Ming; Wang, Yu-Feng; Zang, Yu-Feng; Zhang, Hang (Frontiers in Psychology, 2020)
The reaction time variability is a critical index of sustained attention. However, researchers still lack of effective measures to establish the association between neurophysiological activity and this behavioral variability. Here, the present study recorded reaction time and cortical electroencephalogram (EEG) in healthy subjects when they continuously performed an alternative responding task. The frontal theta activity and reaction time variability were examined trial-by-trial using the measures of standard deviation (SD) in time domain and amplitude of low frequency fluctuation (ALFF) in frequency domain. Our results showed that the SD of reaction time variability did not have any correlation with the SD of trial-by-trial frontal theta activity, and the ALFF of reaction time variability has significant correlation with the ALFF of trial-by-trial frontal theta activity in 0.01-0.027 Hz. These results suggested the methodological significance of ALFF in establishing the association between neurophysiological activity and reaction time variability. Furthermore, these findings also support the low frequency fluctuation as a potential feature of sustained attention.